Policy Analysis Of Closing Level Crossing On The Citayam Road - Rafik Hidayat; Suharto Abdul Majid; Suripno Suripno (STIE Amkop Makassar, 2024)
The level crossing at Citayam Station is located on the Bogor electric train (KRL) line which is strategically located, where around the area there are markets and housing that are currently developing. The high activity in the level crossing area has had an impact on increasing mobilization and economic activities of the surrounding community. Several other supporting mobilizations aside from electric trains (KRL) there are modes of transportation such as public transportation/microbuses, online motorcycle taxis, and base motorcycle taxis. Apart from that, there are street vendors who spread along the road around Citayam Station and pedestrians passing by who want to go to locations around the station. It is this large number of community activities that makes the conditions around the crossing area on the same level as Citayam Station crowded and traffic jams often occur, thus affecting the level of road service. Therefore, a government policy is needed to handle level crossings to eliminate congestion. One of the policies that can be taken by the Government is closing level crossings or building underpasses. By carrying out a road inventory, namely by knowing the geometric conditions of the road and the condition of land use around the road section, the capacity of the road can be calculated. The indicators seen are road width, median width, side obstacle conditions, road shoulder width and road type. In addition to calculating road capacity, it is necessary to process data related to road volume and degree of saturation. So that we get a correlation between these three things and the congestion that occurs. By using multiple linear regression analysis techniques, it can be seen the correlation between the correlation of road capacity, road volume, and degree of saturation (variable x) with congestion that occurs (variable y). So that decisions can be taken regarding government policies to deal with the problem of level crossings.